2020
DOI: 10.1371/journal.pone.0232008
|View full text |Cite
|
Sign up to set email alerts
|

Meeting radiation dosimetry capacity requirements of population-scale exposures by geostatistical sampling

Abstract: Background Accurate radiation dose estimates are critical for determining eligibility for therapies by timely triaging of exposed individuals after large-scale radiation events. However, the universal assessment of a large population subjected to a nuclear spill incident or detonation is not feasible. Even with high-throughput dosimetry analysis, test volumes far exceed the capacities of first responders to measure radiation exposures directly, or to acquire and process samples for follow-on biodosimetry testi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Increasing the numbers of neighbors to 5 reduced the occurrence of these artifacts without negatively impacting the accuracy of the contour map. We have previously demonstrated that circumscribing the boundaries of analyzed regions by specifying these locations with zero counts improves kriging accuracy, especially at locations proximate to boundaries 31 . This approach was used in the present study of interpolated COVID-19 cases for each municipality in Ontario.…”
Section: Geostatistical Analysismentioning
confidence: 99%
“…Increasing the numbers of neighbors to 5 reduced the occurrence of these artifacts without negatively impacting the accuracy of the contour map. We have previously demonstrated that circumscribing the boundaries of analyzed regions by specifying these locations with zero counts improves kriging accuracy, especially at locations proximate to boundaries 31 . This approach was used in the present study of interpolated COVID-19 cases for each municipality in Ontario.…”
Section: Geostatistical Analysismentioning
confidence: 99%
“…The acquisition of said samples, the preparation of metaphase cells and the capture of DC images makes the testing of entire populations logistically impossible. Sampling and testing requirements can be reduced via geostatistical sampling [39]; a method of estimating the spatial boundaries of a region using a small subset of samples at various locations. Applying such methods can limit the number of patients requiring testing while reducing sampling time required for first responders, expediting identification of those requiring treatment in scenarios where time and resources are limited.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that circumscribing the boundaries of analyzed regions by specifying these locations with zero counts improves kriging accuracy, especially at locations proximate to boundaries. 31 This approach was used in the present study of interpolated COVID-19 cases for each municipality in Ontario. Municipal borders were derived by combining all PCs associated with the region of interest.…”
Section: Empirical Bayesian Kriging Analysismentioning
confidence: 99%